2021
DOI: 10.1002/acn3.51328
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary transthyretin amyloidosis in mainland China: a unicentric retrospective study

Abstract: Objective This study aims to report the genotypes and phenotypes of hereditary transthyretin amyloidosis (ATTR) in a large Chinese cohort, yet the clinical and genetic profiles of ATTR remain elusive in mainland China. Methods Fifty‐four patients with molecularly confirmed ATTR from 39 unrelated families were identified by sequencing the TTR gene. Sural nerve biopsies were performed in 40 of these cases. The clinical and electrophysiological data were retrospectively collected and analyzed. Results The male/fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…More importantly, patients in our cohort had much severe autonomic neuropathy such as bladder dysfunction and constipation, which is very rare in classical CMT ( Laurá et al, 2019 ). While 90.7% of the patients with TTR-FAP showed autonomic dysfunction mainly presenting as gastrointestinal involvement including alternative diarrhea and constipation, orthostatic hypotension and urinary dysfunction, however, were reported in only 27.8% of TTR-FAP patients ( Du et al, 2021 ). Our findings indicated that NOTCH2NLC -related IPN was a distinct phenotype of hereditary polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, patients in our cohort had much severe autonomic neuropathy such as bladder dysfunction and constipation, which is very rare in classical CMT ( Laurá et al, 2019 ). While 90.7% of the patients with TTR-FAP showed autonomic dysfunction mainly presenting as gastrointestinal involvement including alternative diarrhea and constipation, orthostatic hypotension and urinary dysfunction, however, were reported in only 27.8% of TTR-FAP patients ( Du et al, 2021 ). Our findings indicated that NOTCH2NLC -related IPN was a distinct phenotype of hereditary polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Inherited peripheral neuropathy (IPN) represents a large heterogenous group of hereditary diseases including hereditary motor and sensory neuropathy (HMSN), more commonly called Charcot–Marie–Tooth disease (CMT), hereditary sensory and autonomic neuropathy (HSAN), distal hereditary motor neuropathy (dHMN), and small fiber neuropathies (SFN) ( Schröder and Matthiesen, 1985 ; Eggermann et al, 2018 ). There are also other forms of IPN such as transthyretin familial amyloid polyneuropathy (TTR-FAP), a severe hereditary neuropathy affecting the sensorimotor and autonomic function as well as other organs caused by mutation of the TTR gene ( Adams et al, 2017 ; Du et al, 2021 ). With the development of next-generation sequencing (NGS) technologies, including disease-target gene panels, whole-exome sequencing (WES), whole-genome sequencing (WGS), and high-throughput transcriptome sequencing, more than 100 and 30 genes have been associated with CMT and dHMN, respectively ( Laurá et al, 2019 ; Pipis et al, 2019 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ATTRA97S is mostly endemic in Taiwan (Han-Taiwanese) with male predominance [7][8][9][10]. It is also a common TTR mutation in mainland China (Han-Chinese), particularly in southern China [17][18][19][20]. One study from Malaysia reported ATTRA97S-PN in nine Chinese Malaysian patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, symptomatic patients were not restricted to late adulthood and elderly individuals. Patients' symptoms may start in their early 30 s. A review of the English literature in the PubMed search engine revealed 12 clinical studies with clinical data (including case reports) of ATTRA97S-PN [6][7][8][9][10][17][18][19][20][21][22][23]. The first case was reported in 1999 [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation